Social Reality in the Light of Values - Topekha, Tatiana; Bolshakova, Natalia; Fedotova, Vera (International Journal of Economics and Financial Issues, 2016)
In the given work the authors try to give an objective scientific analysis of social reality which is in the focus of many investigators today. The article demonstrates possibility of using the system of values to analyze social systems and social reality. It is in the value system, on the one hand, where internalized values of social objects and phenomena are accumulated, and on the other hand it is the source of social creativity reflecting the process of externalization of accumulated values of social objects and phenomena. Sociological research “Family and Personality” conducted in 2012 is considered. A group of people of different age, gender and educational level took part in it. Secondary analysis of its materials points to opportunity of investigating social systems of macro and micro levels, as well as modeling the social reality of a particular society through the system of values existing in it. Keywords: social reality, system, values, value system, shadow value JEL Classifications: C62, O18, P13